ANALISIS KRITERIAPERBANKAN DALAM SISTEM BANK UMUM KELOMPOK USAHA (BUKU) DI INDONESIA - Sumantri, Bambang Agus (LIPI, 2015)
Writing in this journal is to create a map and analyze the shape of banking in Indonesia both conventional banks and Islamic banks. Wherein analyzing touch it with the type and criteria in a system Banking Commercial Bank Business Group (BOOK) that regulate core capital and scope in respect of the products and activities. Keywords: Bank Umum Konvensional